2019
DOI: 10.29252/jafm.75.253.28771
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Flow Simulation and Cavitation Prediction in a Centrifugal Pump using an SST-SAS Turbulence Model

Abstract: The paper handles the subject of the modelling and simulation of the flow inside a centrifugal pump through non-cavitating and cavitating conditions. Operating under cavitation state is so perilous to a pump and can considerably reduce its lifetime service. Hence, to provide highly reliable pumps, it is essential to comprehend the inner flow of pumps. The investigated centrifugal pump comprises five backward curved-bladed impeller running at 900 rpm. The modelling process started with an unsteady numerical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The results revealed that the calculated cavitation performance curve agreed well with the experimental measurements and the pressure fluctuation induced by cavitation was stronger than that of non-cavitation condition. Ennouri et al [12] investigated the centrifugal pump by scale-adapted simulation (SAS) through non-cavitation and cavitation conditions and the results showed an acceptable agreement with testing data. On the other hand, an effective cavitation model is another fundamental technique for CFD research of cavitation, which can describe the interphase mass transfer between the liquid and vapor phases.…”
Section: Introductionmentioning
confidence: 98%
“…The results revealed that the calculated cavitation performance curve agreed well with the experimental measurements and the pressure fluctuation induced by cavitation was stronger than that of non-cavitation condition. Ennouri et al [12] investigated the centrifugal pump by scale-adapted simulation (SAS) through non-cavitation and cavitation conditions and the results showed an acceptable agreement with testing data. On the other hand, an effective cavitation model is another fundamental technique for CFD research of cavitation, which can describe the interphase mass transfer between the liquid and vapor phases.…”
Section: Introductionmentioning
confidence: 98%
“…When the local pressure is less than the saturated vapor pressure, cavitation (a type of complex multiphase flow) may occur in the centrifugal pump (Ennouri et al 2019). Under most operating conditions, cavitation induces harmful effects and can have detrimental consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding Shinde et al [30], they performed a large eddy simulation of a flow over a wall-mounted cube-shaped obstacle placed in a spatially evolving boundary layer for the purpose of understanding how variations in the cube height can modify the flow dynamics in the case where the cube is inside the boundary layer. Likewise, Ennouri et al [31] carried out the modelling and simulation of the flow inside a centrifugal pump, under cavitation and noncavitation conditions, using the SST-SAS turbulence model. Similarly, Zakaria et al [32] implemented an experimental study on a flat plate air solar collector.…”
Section: Introductionmentioning
confidence: 99%